قصَّة آدم عليه السلام بين سورتي (البقرة) و (ص) دراسة في السّياق والنظم - Al Jawhar | الجوهر, Kholoud bint Abdul Latif | خلود بنت عبد اللطيف (Imam Mohammad Ibn Saud Islamic University | جامعة الإمام محمد بن سعود الإسلامية, 2023)
The Holy Qur’an remains able to stir minds by excavating its secrets and discovering the subtleties of its eloquence. And when I studied the story of Adam, peace be upon him, in the two surahs: Al-Baqarah and Sura, I found between them similar and different points, and rhetorical structures that are repeated in the two surahs together. As every word, rather every letter, in the Holy Qur’an corresponds to its position, as if this word was only for this position in the Qur’anic systems, and this study shows the aspects of congruence and difference, by focusing on the events of the story, and its style. | يظل القرآن الكريم قادرا على إثارة العقول تنقيبا عن أسراره، و اكتشافا لدقائق بلاغته، و هذا يؤكد خلود إعجازه، و ينماز بإيراده للقصص المتنوعة، و عرضها في معرض بلاغي بديع يتغيا العبر و العظات، مع تكرار بعضها تكرارا يزيد و يؤكد سمو بلاغتها. و حين تدبرت قصة آدم عليه السلام في سورتي: البقرة و ص، وجدت بينهما نقاطا متشابهات و أخر مختلفات، و تراكيب بلاغية تتكرر في السورتين معا، و لكل زيادة مقصد يراد، و هدف يستفاد؛ إذ إن كل كلمة بل كل حرف في القرآن الكريم قار بموقعه، كأنما لم تكن هذه الكلمة إلا لهذا الموقع الذي جاءت عليه في النظم القرآني، و تبين هذه الدراسة أوجه التطابق و الافتراق، من خلال التركيز على أحداث القصة، و أسلوبها.